POSITIVISME SEBAGAI ERA BARU FILSAFAT DAN PENGARUHNYA DALAM KAJIAN SOSIAL ISLAM - Syarifudin Mustafa (STAI DI AL-HIKMAH, 2026)
Positivism has long dominated the development of modern social sciences by emphasizing objectivity, empirical verification, and value neutrality. Within the context of Islamic social studies, this dominance generates complex epistemological tensions, particularly when positivist approaches are employed to analyze Muslim societies that are deeply embedded with normative, spiritual, and transcendental dimensions. Recent international scholarship (2015–2025) indicates a growing reliance on positivist methodologies in Islamic social research, especially through quantitative surveys and statistical analyses, often at the expense of Islamic value-based frameworks and worldviews. This article critically examines positivism as a “new philosophical era” and its influence on the transformation of Islamic social studies from a sociological-empirical perspective. Using a qualitative approach grounded in critical discourse analysis and the sociology of knowledge, this study analyzes selected scholarly works indexed in Scopus and Web of Science published between 2015 and 2025. The findings reveal that positivism functions not merely as a methodological tool but also as an epistemological framework that shapes how Islamic social realities are constructed and interpreted. This article contributes theoretically by offering a critical mapping of the relationship between positivism and Islamic social inquiry and by proposing an integrative epistemological approach that is more sensitive to values, context, and the transcendental dimensions of Islam. Consequently, this study enriches contemporary debates on Islamic social science methodology and opens new pathways for post-positivist and contextually grounded paradigms in Islamic scholarship.